Insight into enhanced acetic acid production from food waste in anaerobic hydrolysis/acidification with Fe3O4 supplementation. (1st August 2022) - Wang, Lanting; Lei, Zhongfang; Zhang, Zhenya; Shimizu, Kazuya; Yuan, Tian; Li, Shengnan; Liu, Siting
Graphical abstract: Highlights: Fe3 O4 accelerated acetate production in anaerobic digestion of food waste. The maximum acetate yield was enhanced by 79 % with 10 g/L of Fe3 O4 addition. Fe3 O4 enhanced anaerobic hydrolysis/acidification and degradation of propionate. Fe3 O4 promoted enzyme activities and electron transfer in hydrolysis/acidification. Fe3 O4 could act as an electron acceptor and contribute to acetic acid production. Abstract: Fe3 O4 supplementation has been reported as a high-efficient approach to enhance biogas production in anaerobic digestion (AD). Volatile fatty acids (VFAs), especially acetic acid (HAc), are considered as important products in acidification process of AD. However, the possible mechanisms involved in promotion effect of Fe3 O4 on HAc production in hydrolysis and acidification processes of AD have not been comprehensively studied. This study first investigated the promotion effect of Fe3 O4 on hydrolysis, acidogenesis and acetogenesis stages of AD and proposed the underlying mechanisms, using food waste (FW) as the feedstock, which is considered as the most suitable substrate for VFAs production. Results indicated that the HAc production (77.38 g-C/kg-VS) was enhanced by 79 % in AD of FW with addition of 10 g/L Fe3 O4 . The duration to reach the maximum HAc production was also shortened from 14 days to 10 days. The AD tests using model substrates revealed that Fe3 O4 enhanced hydrolysis, acidogenesis, and degradation of propionic acid, thus resulting in enhanced HAc production. The enhanced activities of hydrolytic and acid-forming enzymes, and electron transport system (ETS) with Fe3 O4 addition further demonstrated its function as an electron acceptor to stimulate electron transfer and accelerate microbial metabolisms in AD, which contributed to the enhanced HAc production from FW.